Beyond Digital Literacy in Australian Prisons: Theorizing “Network Literacy,” Intersectionality, and Female Incarcerated Students - Hopkins, Susan (2022)
Incarcerated students, especially women and Indigenous Australians in custody, are among the most marginalized, oppressed, and invisible identities in Australian society today. These prison-based university students experience not only multi-layered disadvantages that derive from intersecting experiences of oppression, including race, gender, and class, but they are also further disadvantaged by the experience of incarceration itself, despite their attempts to improve their life chances and social positioning through distance education. This is partly due to the challenges of learning within prison environments, including disruptions, disparities, and disconnections in terms of access to digital technologies, digital literacies, and digital channels. The majority of Australian prisoners have no direct access to the internet, smartphones, or internet-enabled devices which means they are disconnected from social media and other networked communication platforms. Although significant gains have been made in developing and delivering prison-based non-networked digital devices, digital learning platforms and digital education to Australian incarcerated students over the past decade, more work must be done to adequately prepare incarcerated students, with multi-faceted needs, to live and learn as empowered agents within the informational capitalism of the contemporary “network society.” The purpose of this article is to argue for a new form of “network literacy” education over and above “digital literacy” skills for female Australian incarcerated students, through an intersectional theoretical lens which addresses the multidimensional disadvantages experienced by women in custody within Australian prisons.